PERFORMA KESANTUNAN BERBAHASA INDONESIA DARI SEGI PENGGUNAAN PRINSIP KESANTUNAN WALI KOTA DI SUMATERA BARAT - Maiyola, Olin; Ermanto, Ermanto; Agustina, Agustina (Jurnal Bahasa dan Sastra, 2018)
This study aims to describe the performance of the principles of politeness by the Mayor in West Sumatra. Data are collected in the following manner. (1) downloading a video of a Mayor's speech in West Sumatra either from an official dialogue or when the Mayor went to the field, the researchers collected data from July 4, 2017 to July 18, 2017; (2) transcribes all downloaded videos; (3) observing and determining the data that includes the performance of the use of language-based pronunciation principles. The examination of data validation in this study uses a detailed description technique. After the data collected, then analyzed with the following steps. (1) identify and transcribe data, (2) classify, (3) calculate data using formulas; (4) interpret the data; and infer the data. The conclusion of this research is the performance of language politeness by the Mayor in West Sumatra is very good. This is evidenced from the 275 sentences of speech, found sentence according to the principle of language politeness as much as 259 sentences (94.2%), the corresponding sentence consists of in accordance with the maxim of wisdom, generosity, praise, humility, and inferiority, while the unfit ones is in the use of 16 sentence language (5.8%), the inappropriate sentence consists of the maxim of praise, the maxim of humility and the maxim of agreement.Keywords: politeness, oral communication, mayor